The Marginal Utility of Income. - Layard, R; Nickell, S; Mayraz, G (2008)
In normative public economics it is crucial to know how fast the marginal utility of income declines as income increases. One needs this parameter for cost-benefit analysis, for optimal taxation and for the (Atkinson) measurement of inequality. We estimate this parameter using four large cross-sectional surveys of subjective happiness and two panel surveys. Altogether, the data cover over 50 countries and time periods between 1972 and 2005. In each of the six very different surveys, using a number of assumptions, we are able to estimate the elasticity of marginal utility with respect to income. We obtain very similar results from each survey. The highest (absolute) value is 1.34 and the lowest is 1.19, with a combined estimate of 1.26. The results are also very similar for subgroups in the population. Thus, on the basis of our estimates, the marginal utility of income declines somewhat faster than in proportion to the rise in income.